Development of virtual traditional house for interactive real-time navigation - Abu Bakar, Juliana Aida; Chew, Shiaujing; Ooi, Wooisim; Pang, Chongmeng; Abdrahman, Hafizatul H.; Hussin, Hazarotul L. (Penerbit UTM Press, 2015)
Virtual heritage is able to provide visual aesthetics, real-time navigation and interaction to impress and entertain users.This article describes the design and development of three dimensional (3D) virtual heritage to view and navigate the 3D representation of Malay traditional house which is rare to be found today. The Virtual Traditional House allows flexible exploration with real-time navigation in order for users to walkthrough the 3D reconstruction of the house while viewing relevant historical information at certain parts of the house.The process of design and development of Virtual Traditional House is outlined and points of particular importance are explained.The article discusses the preliminary results of user evaluation for Virtual Traditional House.Future work includes extensive user evaluation and to what extend user may absorb the historical information surfaced around the virtual environment.